Enhancing the community resilience knowledge and engagements in sustainability initiatives of vulnerable children through citizen science-oriented non-formal education - Arianne Grace Revilla; Ernesto Jr. Bastida; Justine Joy Sabanal; Maria Archie Cabig; Lynne Orby Bayot; Cesar Galingana; Jhonies Saysi; Bien Anonuevo; Cecilia Raquel Alvaran; Rona Liezl Hernandez (CTU Journal of Innovation and Sustainable Development)
The study examined the impacts of a Citizen Science Approach (CSA) on vulnerable children’s community resilience knowledge and engagement in sustainability initiatives. Thirty (30) children in conflict with the law from the two Bahay Pag-asa Rehabilitation and Transformation centers underwent a series of participatory planning sessions and research training activities as part of non-formal education program with the central emphasis on biodiversity conservation, environmental protection, water security, health system resilience, natural resources management and food security, and waste management, which are sustainability areas of concerns in the City of Dasmariñas, Cavite. Data were collected using surveys, presentations, and focus-group discussions. On the other hand, content analysis, descriptive statistics, and Kirkpatrick’s four levels of training evaluation were employed to analyze the data. Results indicated there was a significant improvement in the vulnerable children’s community resilience knowledge and planned sustainability engagements as they actively participated in determining the causes of various community problems (contributory), analyzing and interpreting data (collaborative), and proposing action plans and working policies for possible research projects (co-creation). Furthermore, training evaluation revealed that vulnerable children were very satisfied with the learning resources, training environment, acquired learning experience, methods of training execution, and mastery of trainers.